Enrolment at primary level: gender difference disappears in Bangladesh - Chowdhury, AMR; Nath, Samir R; Choudhury, Rasheda K. (International Journal of Educational Development, 2019)
In the recent past, there have been a number of new initiatives to improve the access to primary education in many developing countries. Such initiatives, which came from the public, private and non-governmental (NGO) sectors, have resulted in improved performance in various efficiency indicators. This paper reports results from a nationwide study in Bangladesh on the levels and changes in enrolment pattern of children at the primary level. The gross enrolment ratio has reached 107% and the net enrolment rate 77%. Gender gap has disappeared; in fact girls have surpassed boys! However, the increase in enrolment taking place is not at the desired speed; it is less than one percentage point per year. The government is still the major provider of primary education with two-thirds of all enrolments, but non-formal schools run by NGOs also have important contributions to the positive changes that are taking place in Bangladesh.